Clinical study of anti-snake venom blockade in the treatment of local tissue necrosis caused by Chinese cobra (Naja atra) bites. - Linsheng Zeng; Jingjing Hou; Cuihong Ge; Yanjun Li; Jianhua Gao; Congcong Zhang; Peiying Huang; Jiayu Du; Zhizhun Mo; Yuxiang Liu; Zhongyi Zeng (Public Library of Science (PLoS), 2022)
Objective This study aimed to evaluate the clinical therapeutic efficacy of anti-snake venom serum blockade in treating local tissue necrosis caused by Chinese cobra (Naja atra) bites. Methods Patients bitten by a Chinese cobra (Naja atra) (n = 50) that met the inclusion criteria were randomly divided into two groups: the experimental group (n = 25) and the control group (n = 25). The experimental group received regular as well as anti-snake venom serum blocking treatment, whereas regular treatment plus chymotrypsin blocking therapy was given to the control group. The necrotic volumes around snake wounds in these groups were detected on the first, third and seventh days. On the third day of treatment, some local tissues in the wounds were randomly selected for pathological biopsy, and the necrosis volume of the local tissue was observed. Furthermore, the amount of time required for wound healing was recorded. Results On the third and seventh days post-treatment, the necrotic volume of the wound of the experimental group was much smaller than that of the control group, and the experimental group's wound healing time was shorter than that of the control group (all p < 0.05). Moreover, the pathological biopsies taken from the control group showed nuclear pyknosis, fragmentation, sparse nuclear density, and blurred edges, and the degree of necrosis was much higher than that of the experimental group. Conclusions Anti-snake venom blocking therapy is a new and improved therapy with good clinical effect on local tissue necrosis caused by Chinese cobra bites; moreover, it is superior to conventional chymotrypsin blocking therapy in the treatment of cobra bites. It can better neutralize and prevent the spread of the toxin, reduce tissue necrosis, and shorten the course of the disease by promoting healing of the wound. Furthermore, this treatment plan is also applicable to wound necrosis caused by other snake toxins, such as tissue necrosis caused by elapidae and viper families. Clinical trial registration This trial is registered in the Chinese Clinical Trial Registry, a primary registry of International Clinical Trial Registry Platform, World Health Organization (Registration No. ChiCTR2200059070; trial URL:http://www.chictr.org.cn/edit.aspx?pid=134353&htm=4).